INCREASING STUDENTS' LEARNING MOTIVATION TO ACHIEVE THEIR GOALS THROUGH EDUCATIVE STORIES - Nursafirayanti, Tazkia; Azizah, Siti Nur (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
Education is one of the assets that humans can live in a complex and increasingly developing era. Education aims to humanize humans so that they can be independent in their life path. Educational goals will only be achievable with incentives to motivate students' enthusiasm for learning. The importance of learning motivation to achieve a goal needs to be considered by society in general and teachers in particular. The method of delivering material in professional tales interspersed with icebreaking is used so that students are interested and can quickly grasp the material's content. The output from this activity is that students are expected to have goals that will spur their learning motivation in the educational process.